1999
DOI: 10.1023/a:1006261731125
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of immunocytochemistry, reverse transcriptase polymerase chain reaction, and nucleic acid sequence–based amplification for the detection of circulating breast cancer cells

Abstract: Detection of tumor cells in blood and bone marrow is increasingly used for the staging of patients with breast cancer and to evaluate the presence of tumor cells in peripheral blood progenitor cell collections to be used after high-dose therapy. We evaluated the sensitivity and specificity of three different methods for detection of tumor cells among non-tumor tissue. An immunocytochemical assay using antibodies directed against epitopes of the cytokeratin-19 (CK19) protein and two RNA-based methods: reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 33 publications
0
43
0
2
Order By: Relevance
“…Based on experiences it is unlikely that false positive results can be avoided if only a single marker gene is used in a RT -PCR based test system (Lambrechts et al, 1999). Using more than a single marker gene, as applied in our experiments, is a potential way to overcome the problem of illegitimate expression (Chelly et al, 1989), assuming that there is a little chance of encountering significant illegitimate mRNA of more than one gene at a time.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on experiences it is unlikely that false positive results can be avoided if only a single marker gene is used in a RT -PCR based test system (Lambrechts et al, 1999). Using more than a single marker gene, as applied in our experiments, is a potential way to overcome the problem of illegitimate expression (Chelly et al, 1989), assuming that there is a little chance of encountering significant illegitimate mRNA of more than one gene at a time.…”
Section: Discussionmentioning
confidence: 96%
“…In total, 1 mg total RNA was used for cDNA synthesis (20 ml), as described previously (Lambrechts et al, 1999).…”
Section: Rna Isolation and Quantitative Real-time Pcrmentioning
confidence: 99%
“…Additionally, a recent RT‐PCR system has the ability to assess multiple gene expressions for the detection of CTC in one run. However, several investigators identified some limitations in the clinical application of RT‐PCR assays to the detection of CTC 15, 16. False‐positive results associated with RT‐PCR may be yielded as a result of the illegitimate expression of targeted genes by normal cells and epidermal contamination in blood collecting or processing 15.…”
Section: Detection Of Ctcmentioning
confidence: 99%
“…However, several investigators identified some limitations in the clinical application of RT‐PCR assays to the detection of CTC 15, 16. False‐positive results associated with RT‐PCR may be yielded as a result of the illegitimate expression of targeted genes by normal cells and epidermal contamination in blood collecting or processing 15. Furthermore, false‐negative results may be obtained as a result of the heterogeneous expression of the targeted markers 16.…”
Section: Detection Of Ctcmentioning
confidence: 99%
“…Since NASBA amplifies RNA using an RNA T7-polymerase promoter to generate multiple RNA products at 418C, double stranded DNA is not denatured and consequently not amplified ( Figure 1B) (Chan and Fox, 1999;Simpkins et al, 2000). NASBA has traditionally been used for the amplification of blood-borne viruses (Kievits et al, 1991;van Gemen et al, 1993), though it may also be useful for the detection of circulating tumour cells (Lambrechts et al, 1998(Lambrechts et al, , 1999. Potentially NASBA has two powerful advantages over RT -PCR for the molecular detection of circulating tumour cells.…”
mentioning
confidence: 99%